The Application of 3D Virtual Reality (VR)-Based Learning Media to Improve Cognitive Learning Outcomes in Grade 5 IPAS at SDN 2 Dukuhwaluh - Azqiya, Aida Nur (UM Purwokerto Press, 2025)
In the era of the 4.0 industrial revolution, teachers are not only tasked with conveying information, but also with helping students by utilizing technology. One of the problems in elementary school learning is the lack of student interest in the subject matter, especially when the learning media used is monotonous. This study aims to improve the cognitive learning outcomes of fifth-grade students at SDN 2 Dukuhwaluh in the subject of Integrated Science and Technology (IPAS) through the application of three-dimensional learning media based on Virtual Reality (VR) with the assistance of a VR Box. This research is a Classroom Action Research (CAR) consisting of three cycles. Each cycle includes four stages: planning (plan), implementation of actions (act), observation (observe), and reflection (reflect). Data collection methods include tests, observations, and documentation. Tests are used to gather data on students' cognitive learning outcomes, while observations are used to monitor students' learning activities during the learning process. Additionally, documentation is used to support visual data of learning activities. The research results indicate that the application of VR media can improve students' learning outcomes. The average student score increased from 60.6 in Cycle I to 77 in Cycle II, and reached 84.5 in Cycle III. The study concluded that the application of three-dimensional learning media based on Virtual Reality (VR) can improve the cognitive learning outcomes of fifth-grade students at SDN 2 Dukuhwaluh.